The Effects of Cutting Heights and Intervals of Defoliation on Productivity and Nutrient Content of Brachiaria humidicola(Rendle) Schweick - Selvie Diana Anis; Muhamad Ahmad Chozin; Soedarmadi Hardjosoewignyo; Munif Ghulamahdi; , Sudradjat (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
The productivity of forage is strongly influenced by cutting height and interval of defoliation. Experiment was conducted at the Research Institute for Industrial Plants and Other Palm (BALITKA) Manado since June 2008 until April 2009. The objective of the experiment was to find out the effects of intensity and intervals of defoliation on dry weight production and the quality of nutrients. The experiment was arranged in factorial RCBD. The intensity of defoliation was based on cutting height, i.e. 5, 10, 15 cm, whereas the intervals of defoliation were 30, 45, 60 day and 456.54 Degree Days (DD). The data of dry weight production, leaf stem ratio, nutrient quality were collected. The results showed that there were significant effects of treatments on all parameters. Productivity of B. humidicolai terms of high dry weight yield, high leaf stem ratio and crude protein, low crude fiber and acid detergent fiber (ADF) content were found in the interaction of intensity 10 cm with the interval of defoliation among the vegetative development stage of 30 and 45 days, as well as the interval of defoliation based on heat unit accumulation of 456.54 DD. The research implies that a cutting height at 10 cm and interval of defoliation as mentioned above is ideal for B. humidicola. Utilization of growing degree days (GDD) to determine the appropriate time for defoliation is considerable under this experiment.Keywords: B. humidicola, defoliation, forage, nutrient, productivity